CLIENTELISTIC ORGANIZATIONAL PRACTICES IN NORTHEAST BRAZIL - Joysi Moraes (Faces: Revista de Administração, 2015)
This paper presents an analysis of the management practices in a multinational company located in Northeastern Brazil, considered in the light of one of the  predominant features of social relations the regional culture, clientelism/coronelismo. The research consisted of two stages, a survey and a case study. In the first stage, as a total of 3,000 workers were involved, we chose to perform sampling in which a simple random probability sample was obtained with a confidence level of 90%. In the second stage, we carried out semi-structured interviews and direct observation, allowing a broader view of the field under study. Based on the results obtained, we tried to make analogies between aspects of the regional culture and organizational practices observed in the company. Organizational practices typical of the ‘old’ Brazilian clientelism/coronelismo were found to persist, though wearing new clothes. The manager of a modern organization is representative of the old “Coronel”, reformed by developmental and technological processes.